ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA PT BUMI RESOURCES TBK PERIODE 2018-2021 - Azahra, Adinda Putri (Jurnal Akuntansi dan Bisnis, 2022)
Financial Ratio Analysis is very important in a company to know or measure the company's performance. The purpose of this study is to find out how the financial performance of PT Bumi Resources Tbk. The problem studied is the condition of the financial performance of PT Bumi resources Tbk from 2018 to 2021. By using financial ratio analysis tools that include liquidity ratios, solvency ratios, and profitability ratios. This research uses descriptive methods and quantitative approaches by analyzing the annual financial statements of PT. Bumi Resources Tbk from 2018-2021 obtained through the Indonesian Stock Exchange homepage.In general, the results of the analysis show that the condition of PT Bumi Resources Tbk fluctuates, but it can be said that it is still not good in its efficiency. This means that the company has a poor level of financial performance. Keywords: Financial Performance; Financial Ratios; Bumi Resources Tbk.